1997
DOI: 10.1074/jbc.272.43.26959
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the δ Opioid Receptor:

Abstract: Dimerization of G-protein-coupled receptors has been increasingly noted in the regulation of their biological activity. However, its involvement in agonist-induced receptor internalization is not well understood. In this study, we examined the ability of mouse ␦-opioid receptors to dimerize and the role of receptor dimerization in agonist-induced internalization. Using differentially (Flag and c-Myc) epitope-tagged receptors we show that ␦-opioid receptors exist as dimers. The level of dimerization is agonist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
138
2

Year Published

1999
1999
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 436 publications
(162 citation statements)
references
References 31 publications
13
138
2
Order By: Relevance
“…However, a study on the ␦ opioid receptor suggested that the transition between the oligomeric and monomeric forms of the receptor could be an important step in the internalization process (24). In addition, Herbert et al (23) have suggested that oligomers constitute the active form of the ␤2-adrenergic receptor.…”
mentioning
confidence: 99%
“…However, a study on the ␦ opioid receptor suggested that the transition between the oligomeric and monomeric forms of the receptor could be an important step in the internalization process (24). In addition, Herbert et al (23) have suggested that oligomers constitute the active form of the ␤2-adrenergic receptor.…”
mentioning
confidence: 99%
“…These findings suggest that significant functional interactions may take place between -and ␦-opioid receptors in specific neuronal pathways in brain. We and many other groups have described dimers and oligomers for many GPCRs 1 mediating the actions of neurotransmitters, such as dopamine (9 -12) and serotonin (13), and for neuropeptide receptors, such as vasopressin (14) and opioid peptides (15). Dimerization of the ␦-opioid receptor has been suggested to have an important role in activation and internalization of the receptor (15).…”
mentioning
confidence: 99%
“…The molecular mechanism of receptor oligomerization varies among different receptors and involves transmembrane (TM) domains as well as extramembrane regions. Cysteine residues in the fourth TM segment are responsible for D2 dopamine receptor dimerization (4), and disulfide bonds are also involved in the oligomerization of Ca 2ϩ (22), -opioid (13), sphingosine 1-phosphate (23), and V2 vasopressin receptors (18); sequences in the N-terminal extracellular domains are involved in mGluR (17) and CCR5 (24 -27) homodimer formation; the C-terminal region is essential for ␦-opioid receptor dimerization (12). The seventh TM domain controls noncovalent hydrophobic interactions for adrenergic receptors, which also require receptor glycosylation (7,8).…”
mentioning
confidence: 99%
“…Receptor oligomerization has functional implications in terms of cell surface expression, ligand binding, signaling, and receptor trafficking (1). Many different GPCRs have been proved to undergo homoor heterodimer formation; these include the receptors for dopamine which can form both homo-(2-4) and heterodimers with somatostatin receptors (5), angiotensin A1 and A2 (6), adrenergic (7,8), GABA B (9 -11), ␦-and -opioid (12)(13)(14)(15), rhodopsin (16), mGlu (17), vasopressin V2 (18), vasopressin/ossitocin (19), muscarinic (20), glucagon (21), Ca 2ϩ (22) sphingosine 1-phosphate (23), and the chemokine CXCR4, CCR2, and CCR5 receptors (24 -28). The molecular mechanism of receptor oligomerization varies among different receptors and involves transmembrane (TM) domains as well as extramembrane regions.…”
mentioning
confidence: 99%